Reviewing dengue: still a neglected tropical disease? - Horstick, Olaf; Tozan, Yeşim; Wilder-Smith, Annelies (PLoS neglected tropical diseases, 2015)
Dengue is currently listed as a “neglected tropical disease” (NTD). But is dengue still an NTD or not? Classifying dengue as an NTD may carry advantages, but is it justified? This review considers the criteria for the definition of an NTD, the current diverse lists of NTDs by different stakeholders, and the commonalities and differences of dengue with other NTDs. We also review the current research gaps and research activities and the adequacy of funding for dengue research and development (R&D) (2003-2013). NTD definitions have been developed to a higher precision since the early 2000s, with the following main features: NTDs are characterised as a) poverty related, b) endemic to the tropics and subtropics, c) lacking public health attention, d) having poor research funding and shortcomings in R&D, e) usually associated with high morbidity but low mortality, and f) often having no specific treatment available. Dengue meets most of these criteria, but not all. Although dengue predominantly affects resource-limited countries, it does not necessarily only target the poor and marginalised in those countries. Dengue increasingly attracts public health attention, and in some affected countries it is now a high profile disease. Research funding for dengue has increased exponentially in the past two decades, in particular in the area of dengue vaccine development. However, despite advances in dengue research, dengue epidemics are increasing in frequency and magnitude, and dengue is expanding to new areas. Specific treatment and a highly effective vaccine remain elusive. Major research gaps exist in the area of integrated surveillance and vector control. Hence, although dengue differs from many of the NTDs, it still meets important criteria commonly used for NTDs. The current need for increased R&D spending, shared by dengue and other NTDs, is perhaps the key reason why dengue should continue to be considered an NTD.
Gesehen am 14.09.2020